2015
DOI: 10.1007/s13277-015-4036-4
|View full text |Cite
|
Sign up to set email alerts
|

Presence of tumour high-endothelial venules is an independent positive prognostic factor and stratifies patients with advanced-stage oral squamous cell carcinoma

Abstract: Background: Staging of oral squamous cell carcinoma is based on the TNM system, which has been deemed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 38 publications
2
39
0
1
Order By: Relevance
“…Here, we show that sialyl 6‐sulfo LeX‐expressing HEV‐like vessels are induced in 65.9% of OSCC cases examined and report that these sialyl 6‐sulfo LeX‐positive HEV‐like vessels are induced more frequently in early compared to advanced OSCC. This finding is in line with a recent report by Wirsing and colleagues demonstrating that sialyl 6‐sulfo LeX‐positive HEV‐like vessels were present in all early OSCC cases examined but in two‐thirds of advanced cases . Martinet and colleagues previously reported that HEV‐like vessels are induced in lymphocyte‐rich areas of breast carcinoma and that vessel density is positively correlated with a favorable prognosis .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Here, we show that sialyl 6‐sulfo LeX‐expressing HEV‐like vessels are induced in 65.9% of OSCC cases examined and report that these sialyl 6‐sulfo LeX‐positive HEV‐like vessels are induced more frequently in early compared to advanced OSCC. This finding is in line with a recent report by Wirsing and colleagues demonstrating that sialyl 6‐sulfo LeX‐positive HEV‐like vessels were present in all early OSCC cases examined but in two‐thirds of advanced cases . Martinet and colleagues previously reported that HEV‐like vessels are induced in lymphocyte‐rich areas of breast carcinoma and that vessel density is positively correlated with a favorable prognosis .…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Wirsing et al reported that the presence of HEV‐like vessels in OSCC tissues is associated with lower disease‐specific death and that these HEV‐like vessels are more frequently induced in early (T1/T2) than in advanced (T3/T4) stages, suggesting that lymphocytes recruited via these vessels may function as cytotoxic effector cells to inhibit OSCC tumor growth . However, the extent to which such cytotoxic T cells are recruited through HEV‐like vessels remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…High-endothelial venules are present in secondary lymphoid organs, and develop regularly in chronically inflamed tissue [15]. We have previously reported that the presence of high-endothelial venules is associated with improved survival in oral squamous cell carcinomas [16], which is in line with results from studies on melanoma and breast cancer [17,18]. However, these vessels are plastic, and their remodeling into regular blood vessels may impair lymphocyte recruitment and precede sentinel lymph node metastasis [19,20].…”
Section: Introductionmentioning
confidence: 55%
“…Sixty-eight percent of the patients received surgery in combination with radiotherapy, 15% concomitant radiotherapy and chemotherapy, 11% surgery in combination with local neck-dissection, 5% none or palliative therapy, and 1% were unknown. We retrieved clinical and histopathologic information from the patients' hospital files, pathology reports, and the Statistics of Norway, Cause of Death Registry, and have earlier published these data in studies analyzing the same patient cohort [16,30]. Pathological tumor staging was determined according to the most recent (second to fifth) TNM classification from the American Joint Committee on Cancer at the time of diagnosis.…”
Section: Patients and Materialsmentioning
confidence: 99%
See 1 more Smart Citation